Comparative pharmacokinetics of theophylline in camels (Camelus dromedarius) and goats (Caprus hircus) - Elsheikh, H.A.; Ali, B.H.; Zahurin, M.; Mustafa, A.M.; Alhadrami, G.; Bashir, A.K. (Blackwell Wissenschafts-Verlag, 2001)
A comparative randomized crossover study was conducted to determine the pharmacokinetics of theophylline in male and female camels (Camelus dromedarius) and goats (Caprus bircus). Theophylline is an established 'probe drug' to evaluate the drug metabolizing enzyme activity of animals. It was administered by the intravenous (i.v.) route and then intramuscularly (i.m.) at a dose of 2 mg/kg. The concentration of the drug in plasma was measured using a high-performance liquid chromatography (HPLC) technique on samples collected at frequent intervals after administration. Following i.v. injection, the overall elimination rate constant (λz) in goats was 0.006 ± 0.00076/min and in camels was 0.0046 ± 0.0008/min (P < 0.01). The elimination half-life (t1/2λz) in goats (112.7 min) was lower than in camels (154.7 min) (P < 0.01). The apparent volume of distribution (Izz) and the total body clearance (Cl) in goats were 1440.1 ± 166.6 ml/kg and 8.9 ± 1.4 ml/min/kg, respectively. The corresponding values in camels were 1720.3 ± 345.3 ml/kg and 6.1 ± 1.0 ml/min/kg, respectively. Alter i.m. administration, theophylline reached a peak plasma concentration (Cmax) of 1.8 ± 0.1 and 1.7 ± 0.2 μg/ml at a post-injection time (Tmax) of 67.5 ± 8.6 and 122.3 ± 6.7 min in goats and camels, respectively. The mean bioavailability (I.) in both goats and camels was 0.9 ± 0.2. The above data suggest that camels eliminate theophylline at a slower rate than goats.